Respuesta :

Answer:

= − 2/3

Step-by-step explanation:

Distribute

3x(2x - 3)-6x² =6

6x² -9x-6x² =6

Combine like terms

6x² -9x-6x²=6

-9x=6

Divide both sides of the equation by the same term

-9x=6

-9x/-9=6/-9

Simplify

x=-2/3

Solution

x=-2/3

Answer:

Step-by-step explanation:

3 x (2x - 3) -6x² = 6

6 x^-9x-6x^=6

Combine like terms

6x^-9x-6x^=6

-9x=6

Divide both sides of the equation by the same term

− 9 = 6

-9x = 6

-9     -9

Simplify

Cancel terms that are in both the numerator and denominator

Divide the numbers

=  −2

      3

HOPE IT IS HELPFUL

MARK ME AS BRAINLIEST